Development of postbiotic supplemented polylactic acid films for improving quality and shelf life of rainbow trout - Fatemeh Mosallaie; Fereshteh Falah; Farideh Tabatabaei Yazdi; Seyed Ali Mortazavi; Alireza Vasiee (Scientific Reports)
Abstract Bioactive metabolites derived from lactic acid bacteria (LAB), commonly referred to as postbiotics, have recently attracted increasing interest in the realm of food packaging. In the present study, biopolymeric films incorporated with postbiotics of Lactococcus lactis were produced using polylactic acid (PLA). The fabricated films were characterized in terms of physicochemical, optical, mechanical, structural, and morphological characteristics. Additionally, the effect of the coating on the quality and shelf life of rainbow trout fillets during the seventh day of refrigerated storage was examined. The findings indicated that the values of pH, °Brix, and antioxidant activity, as measured by the DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging assay, were 4.57, 4.80, and 39.29%, respectively. Furthermore, the film incorporated with postbiotic (PLA-POST) exhibited no antibacterial activity against the tested pathogens. Treatment of the films with postbiotic resulted in increased values of thickness, moisture content, turbidity, a * , b * , ΔE*, and elongation at the breakpoint compared to the PLA films. The functional groups and chemical bonds of PLA and PLA-POST films were recorded using Fourier transform infrared spectroscopy (FTIR). Moreover, thermal analysis indicated that the supplementation of postbiotics enhanced the thermal stability of the films (p < 0.05). Field emission scanning electron microscopy (FE-SEM) micrographs of films also revealed that the addition of postbiotics created a rougher appearance with microclusters. In the study, a postbiotic coating for fish fillets was also developed. During refrigerated storage, no differences were found in color, microbiological, and sensory characteristics among the fish samples (p > 0.05). In conclusion, the development of active biodegradable films incorporating postbiotics indicates a promising alternative to traditional petroleum-based packaging materials. Importantly, the use of postbiotics to coat food products, particularly seafood, has demonstrated minimal effects on the sensory characteristics, maintaining their natural flavor, texture, and overall acceptability.